Komunikasi Penyiaran Pada Program Berita “Nusa Tenggara Barat Hari Ini” - Yanti, Komang Yogi; Juniawan, Ida Bagus Heri; Jelantik, Sayu Kadek (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Broadcast communication in the digital era, especially television media, has experienced very strict selection in the last few decades. Media corporations compete fiercely to captivate viewers with news coverage that provides insight and conveys information to the public. The West Nusa Tenggara TVRI News Program still exists to this day, although so far it has received little attention from the public. This research aims to identify the form, process and impact of broadcast communication on the news program "West Nusa Tenggara Today" broadcast by TVRI West Nusa Tenggara. Using a qualitative approach and data collection techniques using non-participant observation and using agenda setting theory to dissect each problem formulation. The research results show that the form of broadcast communication on the news program "West Nusa Tenggara Today" is carried out by verbal communication using language symbols. The communication process occurs when humans interact. The mass communication process is the delivery of messages from communicators to communicants using media as a tool to support the widespread dissemination of information. The impact of the news broadcast is to provide change, namely the knowledge gained. Viewers can obtain the latest information through well-communicated news broadcasts. The negative impact is that the broadcast that is broadcast can cause differences in perception regarding the meaning of the message, which will cause divisions.